2014
DOI: 10.3348/kjr.2014.15.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection of the Rubber Tip of Arrow-Trerotola Percutaneous Thrombolytic Device

Abstract: A rubber tip disconnection of Arrow-Trerotola percutaneous thrombolytic device (PTD) may occur occasionally. We experienced 5 cases of a rubber tip disconnection among 453 mechanical thrombectomy sessions with the use of PTD. We present a report about these five cases and suggest possible causes for the occurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A case series from Kim et al in 2014 reported five instances of disconnection in 453 uses of the device. 12 The disconnections occurred both in fistulae and grafts, and the apparent commonality of each case was activation of the device across a segment of the fistula or graft with an acute angulation. The likely mechanism is fixation of the soft rubber tip during rapid (3,000 rpm) rotation of the fragmentation basket, which then becomes disconnected secondary to material fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…A case series from Kim et al in 2014 reported five instances of disconnection in 453 uses of the device. 12 The disconnections occurred both in fistulae and grafts, and the apparent commonality of each case was activation of the device across a segment of the fistula or graft with an acute angulation. The likely mechanism is fixation of the soft rubber tip during rapid (3,000 rpm) rotation of the fragmentation basket, which then becomes disconnected secondary to material fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous report, rubber-tip disconnection and fragmentation of the rotatory basket were reported during thrombectomy with a rotational PTD device. 36,37 These events occurred in an angulated vessel or indwelling stent or aneurysmal segment. Therefore, careful use of the PTD is recommended in such situations to avoid complications.…”
Section: Discussionmentioning
confidence: 99%
“…Five cases of a rubber tip disconnection were reported among 453 thrombectomies. Those authors experienced a disconnected rubber tip when they activated a PTD within an acute angulated vessel or an indwelled stent ( 26 ). Therefore, careful use of a PTD is highly recommended because there can be complications during thrombectomy and reuse of the device is not recommended.…”
Section: Discussionmentioning
confidence: 99%